Measurement of Health-Related Quality of Life in Primary Antibody-Deficient Patients. (19th May 2017) - Ataeinia, Bahar; Montazeri, Ali; Tavakol, Marzieh; Azizi, Gholamreza; Kiaee, Fatemeh; Tavakolinia, Naiimeh; Negahdari, Babak; Mohammadi, Javad; Abolhassani, Hassan; Rezaei, Nima; Aghamohammadi, Asghar
ABSTRACT: Background : Primary immunodeficiency diseases are a group of disorders that result from a variety of defects of the immune system. Primary antibody deficiencies (PADs) are the most common forms of these disorders. Occurrence of recurrent infections, autoimmune diseases, cancers, and lymphoproliferative disorders is higher in PAD patients. Chronicity of these diseases, delayed diagnosis, inadequate treatment, and treatment side effects may affect the quality of life (QoL) of PAD patients. Evaluating QoL is important for patient care, understanding the burden of these diseases, and finding the patients' major health problems. We investigated the QoL in a group of PAD patients undergoing regular follow-up and treatment at the Children's Medical Center Hospital in Tehran, Iran. Methods : Seventy patients with a diagnosis of PAD in two age groups (younger and older than 18 years) were included. QoL was measured using PedsQL and SF-36 questionnaires. Correlation of demographic, clinical, and immunological parameters with QoL scores was assessed and patients' scores were compared with the normal population, using nonparametric tests of SPSS software. Results : Patients expressed significantly reduced scores in some mental and physical components. Patients with longer follow-up periods had higher scores in mental components but physical component scores were still low. There was no significant correlation between sex, age, and disease types with scores. Conclusions : PAD patients had significantly lower scores in mental and physical components compared to normal population. By early diagnosis and long-term follow-up periods, we may be able to prevent complications and help patients to have a better QoL.